Could tuning of the inhibitory tone involve graded changes in neuronal chloride transport? - Titz, Stefan; Sammler, Esther; Hormuzdi, Sheriar G. (Neuropharmacology, 2015)
Hyperpolarizing synaptic inhibition through GABAA and glycine receptors depends on the presence of the neuronal cation-chloride-cotransporter protein, KCC2. Several transcriptional and post-transcriptional mechanisms have been shown to regulate KCC2 and thereby influence the polarity and efficacy of inhibitory synaptic transmission. It is unclear however whether regulation of KCC2 enables the transporter to attain different levels of activity thus allowing a neuron to modulate the strength of inhibitory synaptic transmission to its changing requirements. We therefore investigated whether phosphorylation can allow KCC2 to achieve distinct levels of [Cl−]i in neurons. We generated a variety of KCC2 alanine dephosphorylation mimics and used NH4+-induced pHi shifts in cultured hippocampal neurons to quantify the rate of KCC2 transport activity exhibited by these mutants. To explore the relationship between KCC2 transport and GABAA receptor-mediated current amplitudes we performed gramicidine perforated-patch recordings. The correlation between EGABA and NH4+-induced pHi shifts enabled an estimate of the range of chloride extrusion possible by kinase/phosphatase regulation of KCC2. Our results demonstrate that KCC2 transport can vary considerably in magnitude depending on the combination of alanine mutations present on the protein. Transport can be enhanced to sufficiently high levels that hyperpolarizing GABAA responses may be obtained even in neurons with an extremely negative resting membrane potential and at high extracellular K+ concentrations. Our findings highlight the significant potential for regulating the inhibitory tone by KCC2-mediated chloride extrusion and suggest that cellular signaling pathways may act combinatorially to alter KCC2 phosphorylation/dephosphorylation and thereby tune the strength of synaptic inhibition.
Gesehen am 02.07.2020